A, The PADAGINGAN DALAM TEKS DEWA TATWA (Perspektif Teologi Hindu): PADAGINGAN DALAM TEKS DEWA TATWA (Perspektif Teologi Hindu) - Wedha, I Wayan Putu Artha; Harsananda, Hari; Suciartini, Ni Nyoman Ayu (Sphatika: Jurnal Teologi, 2024)
Hinduism is such a complex religious teaching that has such a wide range of teachings to learn and will continue to grow with time. One that testifies to the rich teachings of Hinduism is the literary work of religious teachings that is the basis for the execution of every ceremony, behavior, and conduct of human life. One of the most published texts is the text of the god tattwa that contains the teaching of the mekiis ceremony, ngusaba nini, establishes a sanggar tawang, and padagingan at palinggih. The palinggih comes in various shapes to suit the purpose of its construction, but not all of the buildings constructed may be listed as the most palinggih. What might be called the most palinggih is the building that has gone through the sacred stage and given by the spirit into the building. The text of the dewa tattwa is a text that refers to earlier texts of widhitattwa and candi narmada tattwa. It explains how important the blending of the most sophisticated building is. Where the aggregate is a symbol of spirit and an incredible entity that provides a positive vibrational. In practice it isa given material element that can serve as a medium for connecting humans to god.Padagingan is itself composed of components that are wholly meaningful as a symbol of realities that will be intertwined. These symbols are incorporated into a single entity which symbolizes so many manifestations of God that all come from one unthinkable. The symbol provides a basis for confidence in the people who hold such beliefs. The padagingan existence of an outside alloy as a means that brings positive vibrations as well as a medium to increase belief and firmness in carrying out religious teaching.